ADVANTAGES IN COMPARING ENDOSCOPIC AND CONVENTIONAL SURGICAL INTERVENTIONS IN THE BILIARY TRACT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Traditional laparotomy choledocholithotomy, despite the possibility of performing any intervention on the extrahepatic bile ducts, in 1937.7% of cases is accompanied by the development of complications both in the early and late postoperative periods and is generally more difficult for patients than any other interventions [38.77]. Mortality after open interventions on extrahepatic bile ducts, according to a number of authors, reaches 7.8%. This circumstance makes laparotomy choledocholithotomy a less preferred method of treating patients with cholelithiasis complicated by choledocholithiasis, stenosing duodenal papillitis and their combination, limits its use and encourages the search for new ways to solve the problem.